2021
DOI: 10.1016/j.jbc.2021.101224
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiratory chain function promotes extracellular matrix integrity in cartilage

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The highly ordered structure of the ECM endows articular cartilage unique functional properties of cushioning and lubricating joints. Notably, mice with impaired MT electron transport chain proteins had altered ECM composition, resulting in increased cartilage stiffness 37 . MT are highly plastic organelles that undergo morphological and functional changes in response to synthetic and bioenergetic demands 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The highly ordered structure of the ECM endows articular cartilage unique functional properties of cushioning and lubricating joints. Notably, mice with impaired MT electron transport chain proteins had altered ECM composition, resulting in increased cartilage stiffness 37 . MT are highly plastic organelles that undergo morphological and functional changes in response to synthetic and bioenergetic demands 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, clinical studies indicated that cyclosporin A may help to slow COL6-RD progression by correcting the mitochondrial dysfunction [ 43 , 44 , 45 ]. In addition, single-cell (sc) RNA-sequencing analysis demonstrated that mitochondrial respiratory chain dysfunction is a key factor that can alter ECM integrity and mechanostability [ 46 ]. We also detected Golgi apparatus fragmentation and morphological modifications in COL6-RD patient-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The highly ordered structure of the ECM endows articular cartilage unique functional properties of cushioning and lubricating joints. Notably, mice with impaired MT electron transport chain proteins had altered ECM composition, resulting in increased cartilage stiffness (34). MT are highly plastic organelles that undergo morphological and functional changes in response to synthetic and bioenergetic demands (35).…”
Section: Discussionmentioning
confidence: 99%